CHANGES IN FARMER TERMS OF TRADE AND AGRICULTURE NET-BARTER TERMS OF TRADE: AN EMPIRICAL ANALYSIS - Hermanto Siregar (Jurnal Manajemen & Agribisnis, 2004)
In line with the Prebisch-Singerhypothesis, it is found that the Indonesian farmer terms of trade in aggregatefollowed a negative trend. Spatially, this tendency was mainly the case for theWestern Part of Indonesia, whereas in the Eastern Part of the country,especially in some Sulawesi and Kalimantan provinces, the farmer terms of tradeincreased significantly. This shows a potency to properly expand theagricultural sector in these provinces without risking the relative welfare offarmers to decline. Thus more agricultural development efforts should bedevoted to these regions. The net barter terms of trade for agriculture, whichmay be seen as a proxy of relative welfare of farmers with some accesses toexport/import market, on the other hand, generally depict a non-negative trend.This suggest that in average this group of farmers, or perhaps a group ofagricultural exporters, was less severaly affected by the crisis or crisis-likeevents than the peasant farmers. Therefore, systematic development program,which should be more than a rescue-short-term-demand-side program, is neededwith a main aim to stabilize the relative welfare of the peasant. The analysisalso suggests that Indonesiaagricultural exports are supply determined, which means that eliminations ofsupply bottlenecks and technological advancement leading to a lower unit costrelative to price received are necessary to undertake.